2020
DOI: 10.1002/fes3.244
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling growth from phosphorus uptake in Lemna: Implications for use of duckweed in wastewater remediation and P recovery in temperate climates

Abstract: is an essential nutrient for all living organisms which enters the food chain through its acquisition from environmental sources by primary producers. In approximately 50% of agricultural soils, P is limiting for plant growth and supplemental fertilization is required for optimal crop productivity (Lynch, 2011). However, P-rich rock required for inorganic phosphate fertilizer production is a limited, nonrenewable resource (Elser & Bennett, 2011; Steiner, Geissler, Geissler, Watson, & Mew, 2015). Paradoxically,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 58 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…14 The PO 4 3À uptake by the macrophytes and subsequent intracellular storage were demonstrated. [41][42][43] The mass balance in the non-axenic study showed that the uptake of phosphorus by the macrophytes was the dominant mechanism of removal. 43 The movement of P across the root cell requires an energy-driven phosphate transporter to move P through the membranes into the plant root cells.…”
Section: Phosphate Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The PO 4 3À uptake by the macrophytes and subsequent intracellular storage were demonstrated. [41][42][43] The mass balance in the non-axenic study showed that the uptake of phosphorus by the macrophytes was the dominant mechanism of removal. 43 The movement of P across the root cell requires an energy-driven phosphate transporter to move P through the membranes into the plant root cells.…”
Section: Phosphate Removalmentioning
confidence: 99%
“…[41][42][43] The mass balance in the non-axenic study showed that the uptake of phosphorus by the macrophytes was the dominant mechanism of removal. 43 The movement of P across the root cell requires an energy-driven phosphate transporter to move P through the membranes into the plant root cells. 44 Phosphorus is a macronutrient of plants, and the major constituent in adenosine diphosphate (ADP) and adenosine triphosphate (ATP), which are crucial for energy storage and transfer in photosynthesis and respiration.…”
Section: Phosphate Removalmentioning
confidence: 99%
“…It was hypothesized that metals with a high positive correlation are possibly from the same pollution source [81]. P uptake was correlated with P concentration in the media, with more rapid uptake at higher initial concentrations [82,83]. The results show that the correlation coefficient values between ammonium and phosphates were found to be 0.96 and 0.98, respectively, which indicated the impact of the positive correlation with phosphate and ammonium levels [84].…”
Section: Pearson Correlation Of Different Indicatorsmentioning
confidence: 87%
“…Recently, duckweed of Lemna sp. was used for the recovery of P from the wastewater under 8 ˚C temperature and short photoperiod (6 h) conditions (Paterson et al, 2020). This result suggests that use of duckweed for wastewater remediation in temperate conditions is worthy of further exploration, particularly for small and rural communities where access to land is available and affordable.…”
Section: Recapture Of P From Wastewatermentioning
confidence: 95%